2019
DOI: 10.1016/j.ajoc.2019.100512
|View full text |Cite
|
Sign up to set email alerts
|

DMEK outcomes using nondiabetic grafts for recipients with diabetes mellitus

Abstract: Purpose To compare Descemet membrane endothelial keratoplasty (DMEK) outcomes using nondiabetic grafts in diabetic and nondiabetic recipients. Methods All eyes that underwent DMEK between February 2013 and October 2016 (follow-up ≥3 months, without prior keratoplasty) were included. Recipients were divided into diabetic (insulin dependent [IDDM] or noninsulin dependent [NIDDM]) and nondiabetic groups. Main outcome measures included postoperative visual acuity, rebubble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…More recently, the effects of T2DM on CECs have become better understood, especially with respect to endothelial keratoplasty and surgical outcomes. 88,89 Prior to transplant, graft tissues from donors with advanced diabetes have lower than average CEC densities, 90 and 3 years following DSAEK surgery diabetic donor graft tissues display more cell loss compared to nondiabetic control tissues, as well as increased graft failure rates. 91,92 Advanced diabetic donor tissues also have altered extracellular matrix properties impacting their biomechanical stiffness.…”
Section: Decreased Mitochondrial Counts Decreasedmentioning
confidence: 99%
“…More recently, the effects of T2DM on CECs have become better understood, especially with respect to endothelial keratoplasty and surgical outcomes. 88,89 Prior to transplant, graft tissues from donors with advanced diabetes have lower than average CEC densities, 90 and 3 years following DSAEK surgery diabetic donor graft tissues display more cell loss compared to nondiabetic control tissues, as well as increased graft failure rates. 91,92 Advanced diabetic donor tissues also have altered extracellular matrix properties impacting their biomechanical stiffness.…”
Section: Decreased Mitochondrial Counts Decreasedmentioning
confidence: 99%
“…Similarly, Price et al ( 32 ) reported that patients with diabetes experienced more endothelial cell loss after the graft than non-diabetic patients but with no visual consequences. Price also reported that diabetes status is correlated with an increased risk of rebubbling, as did Janson et al ( 33 ). The latter studied the relationship between DMEK outcomes and diabetes in 41 patients with diabetes not on insulin therapy, 22 patients with diabetes on insulin therapy, and 271 controls.…”
Section: Discussionmentioning
confidence: 67%